Raqamli rozilikning haqiqiyligi: elektron tijorat arbitrajida Nyu-York konventsiyasining «yozma shaklda» talabiga rioya qilish - Rabbimova Farahbonu Alisherovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
The enforceability of international arbitral awards arising from cross-border e-commerce transactions is increasingly jeopardized by persistent disparities in jurisdictional standards for determining valid digital assent. While proactive contracting mechanisms—most notably click-wrap agreements—generally satisfy the pro-enforcement requirements of the New York Convention, the passive nature of browse-wrap arrangements frequently fails both the formal “in writing” requirement under Article II(2) and the foundational principle of mutual consent. This article argues that this gap is not merely a procedural inconvenience but a structural threat to party autonomy and, consequently, to the finality of arbitral awards under Article V(1)(a). Crucially, proposals for a harmonized digital assent standard—however compelling in theory—face serious practical obstacles: states have strong sovereignty interests in regulating consumer contracts, and any mandatory international protocol must navigate the tension between commercial efficiency and consumer protection. This article therefore proposes a calibrated Global Model Protocol for Digital Assent under UNCITRAL auspices, mandating active two-step consent, plain-language disclosure, and the categorical exclusion of browse-wrap reliance in cross-border disputes. The proposal is grounded in the argument that such reform is not an optional enhancement but a precondition for the continued legitimacy of international arbitration in the digital economy.